Gel Electrophoretic Determination of Atrial Natriuretic Peptide and its Truncated Peptide - G. Tyagi*, Manoj (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Atrial natriuretic peptide (ANP) is released from the heart and induces the elicitation of guanylate cyclase enzyme activity. It has vasodilatory and natriuretic properties. In this study we elucidated the determination of ANP deoxyribonucleotide (DNA) and its truncated peptide ANP (4-28) by agarose gel electrophoresis. The techniques combined the use of polymerase chain reaction and gel electrophoresis for simple estimation of DNA content from biological samples.